"O avesso da pele", de Jeferson Tenório : uma leitura do corpo/corporeidade das personagens - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This dissertation proposes a historical philosophical reading of the body/corporeality in the book O Avesso da Pele (2020), written by the Brazilian author Jeferson Tenório. The theoretical framework seeks to conceptualize corporeality based on Merleau Ponty’s Phenomenology of Perception (1999). Additionally, we draw on references regarding the construction of body/corporeality in the Wes tern tradition, such as Platão (1991), Saint Augustine (1980), Karl Marx (1991), and Michel Foucault (1999; 2001). To support our research on Black corporeality, we consider the studies of Frantz Fanon (2020a; 2020b), Achille Mbembe (2014; 2018), and Lélia Gonzalez (1980). Our inquiry focuses on two main questions: first, what elements in these characters contribute to the reproduction of social reification as manifested through the body? Second, to what extent do these characters reveal the dimensions of a body whose expressiveness is capable of transcending morally imposed norms, which are subordinated to power relations over the body? These reflections can enrich the debate on the body as a symbol of power, control, and freedom, aligning with critical stu dies on corporeality in Cultural Studies. Tenório demonstrates that overcoming alienation, while possible, is an arduous process shaped by resistance. This liberation comes at a high cost, requiring individuals to confront deeply rooted prejudices and dehu manization. The author emphasizes the need to preserve the "reverse side," that is, the intimate space protected from external judgments, and to value affections, which are often denied to Black people. Although many of these affective relationships are ma rked by social traumas, they become essential forms of resistance. Ultimately, the analysis of these elements in the characters can help us understand how the adjustment of these bodies is portrayed in the narrative and how the characterization of the prot agonists challenges and subverts the imposed norms on the body. These characters can also serve as inspiring models of resistance, highlighting the importance of differences.
"The reverse of the skin" by Jeferson Tenório : a reading of the characters' body/corporeality
Keywords: Corpo; Corporeidade; Personagem; Racismo; Romance; Body; Corporeality; Racism; Character; LINGUISTICA, LETRAS E ARTES::ARTES; LETRAS::LITERATURA BRASILEIRA